2013
DOI: 10.1007/s10517-013-2288-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gold Nanoparticles on Production of Reactive Oxygen Species by Human Peripheral Blood Leukocytes Stimulated with Opsonized Zymosan

Abstract: We studied the effect of gold nanoparticles on ROS production by leukocytes. ROS production was detected by luminol-dependent chemiluminescence (LDCL) of human peripheral blood leukocytes stimulated with opsonized zymosan. Nanoparticle size was 5, 10 and 30 nm. Simultaneous addition of nanoparticles and opsonized zymosan showed that 5-nm nanoparticles inhibited LDCL intensity in comparison with the control, when LDCL recording was conducted in the presence of opsonized zymosan. Increasing nanoparticle size fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…GNRs stabilized with CTAB were found to cause more severe cellular responses than those coated with either thiolated polyethylene glycol 5000 or mercaptohexadecanoic acid 14. Consistent with previous findings that the cytotoxicity of nanoparticles was strongly correlated to their surface charges, the toxicity disparity stemmed from different electrostatic associations between nanoparticles and cell membranes and the membrane‐compromising effects of CTAB 9, 10, 13. C‐GNRs with positive surface charges would electrostatically attach to negatively charged erythrocytes, where (1) binding of CTAB surface of GNRs with the phosphatidyl choline‐rich erythrocyte membrane and (2) bending of the erythrocyte membrane to adapt to the rigid surface of GNRs might occur 15.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…GNRs stabilized with CTAB were found to cause more severe cellular responses than those coated with either thiolated polyethylene glycol 5000 or mercaptohexadecanoic acid 14. Consistent with previous findings that the cytotoxicity of nanoparticles was strongly correlated to their surface charges, the toxicity disparity stemmed from different electrostatic associations between nanoparticles and cell membranes and the membrane‐compromising effects of CTAB 9, 10, 13. C‐GNRs with positive surface charges would electrostatically attach to negatively charged erythrocytes, where (1) binding of CTAB surface of GNRs with the phosphatidyl choline‐rich erythrocyte membrane and (2) bending of the erythrocyte membrane to adapt to the rigid surface of GNRs might occur 15.…”
Section: Resultssupporting
confidence: 87%
“…More erythrocyte toxicities, such as deformation, agglutination, and membrane damage, were extensively reported for some other nanomaterials 8. Although biologically incompatible responses of gold nanoparticles in blood have been noticed before,9 the interaction between GNRs and erythrocytes still needs more investigations. Hemoglobin, as the most abundant protein in erythrocytes, mediates the main physiological functions in erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Of the wide ranging studies describing the biological effects of GNPs, several have reported elevated levels of reactive oxygen species for GNPs of differing size, shape and surface functionalization (Pan et al 2009; Chompoosor et al 2010; Li et al 2010; Piryazev et al 2013; Mateo et al 2014). Comparatively few reports have demonstrated a role for ROS or the involvement of mitochondria as mechanism of GNP radiosensitisation (Geng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the AuNPs also has an impact on the induction of ROS. It was reported that AuNPs of 30 nm could induce more ROS generation than the smaller AuNPs [27]. From TEM images, the sizes of the SD-AuNPs was nonuniform, which might lead to different degrees of interaction between the AuNPs and the cellular membrane of the L929 cells, resulting in different degrees of ROS generation that could impact cell death [28].…”
Section: Reactive Oxygen Species (Ros) Generationmentioning
confidence: 99%